Determination of Protocatechuic Aldehyde in Danshen Injection by Flow Injection Chemiluminescence - Zhao, Shihao; Zhang, Pingping; Feng, Jing (Asian Journal of Chemistry, 2012)
A novel chemiluminescence system for determination of protocatechuic aldehyde with flow injection analysis is described. It is based on the chemiluminescence reaction of potassium ferricyanide and luminol in sodium hydroxide medium. The optimized experimental conditions were evaluated. Under optimum conditions, calibration curve over the range of 1.0-50 mg L-1 was obtained (r = 0.9992). The detection limit of this method was 0.2 mg L-1. The relative standard deviation was 3.4 % for 20 mg L-1 protocatechuic aldehyde. The method has been applied to the determination of studied protocatechuic aldehyde in Danshen injection with a satisfactory result.